Influence of Socio-demographic Factors on Perception of Midline Diastema - B.O. Akinboboye; A.O. Ehizele; T. Esan (Nigerian Dental Association, 2020)
Objective: Socio-demographic factors have been said to affect the perception of midline diastema. Aesthetic importance of maxillary midline diastema varies in individuals and there is no common consensus on the registration of diameter of maxillary midline diastema. The aim of the study was therefore to determine the acceptable width of diastema among a group of Nigerian subjects and the effect of their socio-demographic factors on the perception of midline diastema. Method: Subjects aged 19-45 yrs were recruited from the 6 geopolitical zone of Nigeria. A structured questionnaire was administered to  participants. The questionnaire sought for information such as age, gender, profession, presence of midline diastema and created diastema. The questionnaire included a coloured smile photograph with digitally altered varying sizes of diastema (2mm - 6mm). Subject rated the different coloured photographs using the rating scale (very attractive =1, attractive =2, accepted =3, unattractive =4, and very unattractive =5). Data were analyzed with the Statistical Package for Social Sciences (SPSS) version 16.0 (SPPS Inc, Chicago IL). Result: A total of 374 participants aged 19 - 45 years was involved in this study. Majority (52.1%) were females and mean age was 37.07+/-0.63  years. Only 30.2% had midline diastema out of which 12% was artificially created. Majority (86.7%) of the created diastema was done by the dentist.  Age (p=0.024) and level of education (p=0.017) had a significant relationship with perception of midline diastema. Older subjects and those with lower educational level considered midline diastema a sign of beauty. Majority of the participants perceived the 2-4mm midline diastema attractive and 5-7mm midline diastema unattractive. Conclusion: It can be concluded from this study that a relationship exists between age and perception of midline diastema. The acceptable width of  the midline diastema in this study is 2mm-4mm.